PO24 | Emicizumab prophylaxis and bleeding outcomes: a single center clinical experience (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Emicizumab for hemophilia A (HA) has been increasingly employed in clinical practice. The aim is describing our real-world experience and clinical outcomes in severe HA patients (pts).